PHYSICO-CHEMICAL INDICATORS OF HYDROGELS INCREASING THE INTENSITY OF OIL WELLS AND THEIR ECONOMIC EFFICIENCY - Shirinov Sh.D.; Nazarov S.I.; Shirinov G.K.; Kenzhaeva N.R. (Journal Park Publishing, 2023)
In this article, the physicochemical parameters of hydrogels that increase the efficiency of oil wells and the technology of their application are studied.
Keywords: hydrogel, oil, degree of swelling, toxicological index, polyacrylonitrile, density.